EXPLORING STUDENTS' PERCEPTIONS OF GOOGLE TRANSLATE AS AI-ASSISTED TRANSLATION IN INDONESIAN VOCATIONAL HIGH SCHOOL - Andy Sutrisno; Iman Cahyanto; Ela Meiliasari (Universitas Wiralodra, 2025)
This study examines the utilization of Google Translate as an AI-assisted translation tool by Indonesian vocational high school students in English as a Foreign Language classes. The primary objective was to assess students' perceptions of Google Translate’s efficacy in enhancing their English skills and whether it should supplement or replace traditional teaching methods. Data were collected from a sample of vocational students using a survey approach to assess the tool’s perceived benefits and its frequency and purpose of use. The findings indicate that students often utilize Google Translate to enhance their vocabulary, comprehend challenging material, and verify their grammar, which many assert contributes to increased confidence in speaking English. There were mixed insights into its impact on self-directed learning and enhanced language engagement, with some students utilizing the technology excessively. These results indicate that Google Translate is a valuable tool; nevertheless, educators may need to limit its usage to balance language practice and critical thinking. Future research may investigate the impact of AI translation on specific language skills and its influence on the retention of language proficiency over time. This study enhances the growing research on AI-assisted language learning technologies and their impact on EFL instruction.